The Impact of Trade Policy Uncertainty on Export Enterprises’ Innovation - Ai, Qingsong (Transactions on Economics, Business and Management Research, 2024)
In the context of the complex and variable global trade environment, the importance of cultivating new competitive advantages for foreign trade is gradually highlighted. This directly concerns the development quality of our country’s trade and is the necessary path for enterprises to achieve innovative development. Clarifying the main position of enterprises in technological innovation is key to constructing a high-quality development pattern. However, due to objective factors, such as adjustments in the international environment and the presence of emergencies, the uncertainty of our country’s trade policy has significantly increased, bringing new challenges to the innovation activities of export enterprises. It is essential to analyze from different angles and explore the impact of trade policy uncertainty on the innovation of export enterprises. During the development process of enterprises, the uncertainty of trade policy represents facing higher market impacts and cost pressures. It can also inspire the innovation motivation of enterprises, prompting them to seek new competitive advantages. For the government, how to create favorable conditions for enterprise innovation while ensuring the stability of trade policy is also an important topic. Therefore, this paper’s research helps enterprises better understand the impact of trade policy uncertainty on their innovation activities, thus formulating more reasonable and effective innovation strategies; it also provides useful references for the government in policy-making, helping to create more favorable conditions for the innovative development of our country’s export enterprises in a complex and variable international environment.